Nutritional status of the geriatric population in the field practice area of a medical college in Rajasthan - J. Gandhi, Shreyashkumar; Choudary, Mahesh Kumar; Kumar, Rupesh; Bhatnagar, Dinesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Ageing is a physiological process that starts from birth, continues throughout life, and ends with death. Poor nutrition is not a natural concomitant of ageing; older adults are at risk for malnutrition due to physiological, psychological, social, dietary, and environmental risk factors. The objectives of the study were to assess the nutritional status of elderly living in rural India and to study the factors related to nutritional status. Methods: Community-based cross-sectional study was undertaken in the field practice area of Pacific Medical College and Hospital, Udaipur, Rajasthan. Predesigned and pretested questionnaire and nutritional status were assessed using mini nutritional assessment scale for elderly people. Results: Out of the total 152 participants, 2 (1.3%) were having BMI less than 19, 11 (7.2%) were having BMI 19 to less than 21 and 43 (28.3%) were having BMI 21 to less than 23. Out of 152 participants, 30 (41.1%) males and 43 (54.4%) females were at risk of malnutrition. Six (8.2%) males and 5 (6.4%) females were suffering from malnutrition. However, the association of gender and nutritional status of elderly was not found to be statistically significant (p=0.258). Conclusions: Due to the high prevalence of elderly who were malnourished or at risk of malnutrition, a more detailed evaluation, regular follow up & dietary intervention to reverse the situation is required.